2020
DOI: 10.1016/j.ajo.2020.05.039
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Impact of Residual Amblyopia on Functional Vision and Eye-related Quality of Life Using the PedEyeQ

Abstract: Purpose: To evaluate the effect of residual amblyopia on functional vision and eye-related quality of life (ER-QOL) in children and their families using the Pediatric Eye Questionnaire (PedEyeQ). Design: Prospective cross-sectional studyMethods: Seventeen children with residual amblyopia (no current treatment except glasses), 48 visually normal controls without glasses and 19 controls wearing glasses (aged 8-11 years) completed the Child 5-11 year PedEyeQ. One parent for each child completed the Proxy 5-11 Ped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…Our findings accurately outline the clinical reality of postoperative children with congenital and developmental cataracts. For example, we found that nystagmus, strabismus, and amblyopia are all likely to have an impact on peoples' daily activities ( 22 , 28 , 29 ) because reduced visual acuity and stereoacuity all influence their functional vision. Patients with amblyopia are more likely to have a slower reading speed ( 30 ), with those with strabismus being more likely to also exhibit motor skill deficits ( 30 ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Our findings accurately outline the clinical reality of postoperative children with congenital and developmental cataracts. For example, we found that nystagmus, strabismus, and amblyopia are all likely to have an impact on peoples' daily activities ( 22 , 28 , 29 ) because reduced visual acuity and stereoacuity all influence their functional vision. Patients with amblyopia are more likely to have a slower reading speed ( 30 ), with those with strabismus being more likely to also exhibit motor skill deficits ( 30 ).…”
Section: Discussionmentioning
confidence: 97%
“…The factor structure and validity, as well as the known-group, discriminant, and convergent validities, of the PedEyeQ have been established in studies of children with bilateral visual impairment ( 6 ), residual amblyopia ( 22 ), strabismus ( 23 ), unilateral visual acuity deficit ( 24 ), and correlational research between functional measures and the Child PedEyeQ ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has shown that amblyopia not only impacts vision of the affected eye; functional consequences include deficits in the stronger, fellow eye, slow reading, impaired motor skills, and low self-esteem and quality of life (see ''Box'')-all issues that can streamline into a child's everyday life, and persist into adulthood [88,[93][94][95][96][101][102][103][104][105][106][107]. Therefore, it is imperative that this condition be diagnosed and treated as early as possible.…”
Section: What's On the Horizon?mentioning
confidence: 99%
“…Self-Perception and Quality of Life Amblyopia affects children’s self-perception, especially of physical competence and peer acceptance [ 94 96 ]. Children with amblyopia and their parents have reduced quality of life scores [ 107 ]. …”
mentioning
confidence: 99%